A Bio-Diesel Chemical Kinetic Mechanism Based on Decoupling Methodology and Detailed H2/O2/CO/C1 C3 Mechanism - Yang, Shiyou; Jia, Ming (Frontiers in Mechanical Engineering, 2019)
Biodiesel is a renewable, clean-burning diesel replacement, and may have superior brake thermal efficiency with certain blends compared to traditional diesel counterpart at higher compression ratios. The combustion chemistry process of biodiesel, which has not been well understood, is of great interests to some engine researchers. Researchers have developed some complicated chemical kinetic mechanisms for bio-diesel, which cannot be used in engine CFD with current computational resources. The present work aims to construct a new chemical kinetic mechanism with a medium size for biodiesel combustion. Since 2016, H2/O2/CO/C1 and C2-C3 detailed sub-mechanisms (the C3 model contained in AramcoMech2.0) have been developed for accurately predicting laminar flame speeds, ignition delay times, and important species evolutions, and have been validated against a large array of experimental measurements over a wide range of conditions. In this paper, a 3-component biodiesel surrogate chemical kinetic mechanism constructed in 2015 based on decoupling methodology has been combined with the new ‘core’ H2/O2/CO/C1 C3 detailed mechanism to generate a new bio-diesel chemical kinetic mechanism. In the surrogate mechanism construction, three skeletal sub-mechanisms are used for the three biodiesel components (MD, MD5D, and n-decane). The final mechanism, which has 183 species and 1002 reactions, has been validated with available experiment data. It will be validated extensively with more experimental biodiesel data and applied to engine CFD for understanding biodiesel combustion.